(untitled) (diségno, 2023)
The volume Linguaggi Grafici. Decorazione, edited by Enrico Cicalò, Francesca Savini and Ilaria Trizio, deals with a very current topic, especially in the declination that new technologies can offer. The work could not avoid dealing with the topic without considering another issue, which is that of ornament, highlighting the semantic similarity between the two terms and the differences dictated by the etymology of the names, as the editors point out [read more]